2019
DOI: 10.1007/s11051-019-4524-3
|View full text |Cite
|
Sign up to set email alerts
|

What is the problem? A literature review on challenges facing the communication of nanotechnology to the public

Abstract: Ethical and societal issues concerning justice, safety, risks, and benefits are well-established topics in the discourses of nanotechnology innovation and development. That nanotechnology innovation should be socially and ethically responsible is generally accepted by scientists, policymakers, regulators, and industry, and the idea of public involvement and communication is part and parcel of the conceptualization of responsible technology development. This paper systematically reviews the social science resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 87 publications
(141 reference statements)
0
13
0
2
Order By: Relevance
“…Among the participants high on initial dread, those who read the mixed set of comments scored highest on risk perception. This might perhaps be due to the uncertainty or negative affect evoked by the comments of mixed valence (Boholm & Larsson, ). Contrary to expectation, among participants high on initial dread, those who read the negative comments scored lowest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the participants high on initial dread, those who read the mixed set of comments scored highest on risk perception. This might perhaps be due to the uncertainty or negative affect evoked by the comments of mixed valence (Boholm & Larsson, ). Contrary to expectation, among participants high on initial dread, those who read the negative comments scored lowest.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed attitudes toward nanotechnology to be moderately positive across many areas of application. Benefits were expected to occur predominantly in relation to medicines and health, and technological development, rather than to agriculture and food (Boholm & Larsson, 2019;Capon et al, 2015;Conti, Satterfield, & Harthorn, 2011;Frewer, 2017;Frewer et al, 2014;Giles, Kuznesof, Clark, Hubbard, & Frewer, 2015;Priest, 2009;Siegrist et al, 2007;Yue, Zhao, Cummings, & Kuzma, 2015). Food-related applications were also more likely to raise societal concern than other applications, and the application of nanotechnology in food was perceived to be less beneficial than in food packaging (Capon et al, 2015;Siegrist et al, 2007;Siegrist et al, 2008).…”
Section: Nanotechnology: Acceptance and Decisionmakingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, describing a world people cannot see and physically interact needs enhancement of understanding these emerging technologies using science communication/citizen-science to reach its full revolutionary potential. Public attitudes, and reflexive governance are essential to public acceptance of NSNT innovation (Boholm & Larsson, 2019). It is one of the most rapidly growing/broad multidisciplinary fields in science, technology, life sciences and engineering research/innovation and is founded on the convergence of traditional disciplines to create, study, and apply materials at the nanoscale (Holland et al, 2018).…”
Section: Introductionmentioning
confidence: 99%